ANATOMICAL VARIATIONS IN UPPER LIMB ARTERIES - R.Е. КАLININ; I.А. SUCHKOV; N.D. МJAVANADZE; R.М. МUSTAFAEVA (Avicenna Tajik State Medical University, 2017)
Upper extremity arterial disorders are less common than lower extremity disorders. Occlusion and critical stenoses of the arteries lead to the development of ischemia, during which anatomical features of the upper limbs structure play an important role. A large number of anastomoses and a well developed collateral circulation often lead to compensation of blood circulation. During the conducting an open treatment the vascular surgeons meet a non-standard anatomy that presents technical obstacles to the performance. The current article reviews the anatomical variations in upper limbs and formed among them anastomoses which any surgeon may encounter. Having analysed the experiences of colleagues led to the conclusion that the non-classical origin and location of upper limb arteries are a frequent phenomenon that can significantly affect to the medical strategy and change the condition of ischemia of the upper extremities. These data must be taken into consideration in angiographic studies, selection of access during surgical interventions and medical manipulations. Therefore, it is important to conduct a careful examination of each patient to the surgical treatment in order to identify individual characteristics and avoid mistakes.